Bullying di Lingkungan Perguruan Tinggi: Kajian Literatur tentang Toleransi dan Harmoni Sosial - Safira 'Ainul Mardiyyah; Azzahra Zahira Cora Mahza Patria; Salwa Aisyah Silvaratih (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Bullying in higher education institutions is a social issue that disrupts students' comfort, safety, and overall academic environment. This phenomenon not only affects victims' psychological well-being but also hinders the creation of a healthy, inclusive, and supportive learning atmosphere. Although numerous studies have examined bullying, research linking it to the values of tolerance and social harmony remains limited. This study aims to analyze bullying in higher education from the perspectives of tolerance and social harmony. The research employed a Systematic Literature Review (SLR) by examining relevant scientific articles obtained from Google Scholar and other scholarly sources. The findings indicate that the implementation of tolerance through respect for diversity, openness in social interaction, and appreciation of differences can reduce the likelihood of bullying. Furthermore, social harmony fostered through collaboration, inclusive communication, and a culture of mutual respect contributes to creating a safe campus environment. Conversely, a culture of seniority, weak institutional supervision, and permissive attitudes toward bullying increase the risk of such behavior. Therefore, comprehensive institutional policies, secure reporting mechanisms, psychological support services, and continuous educational programs are essential to strengthen tolerance and social harmony, ultimately creating an inclusive, safe, and bullying-free higher education environment.